Beyond the Narrative: Estado da Índia Renegades Under Historical and Philosophical Perspective - Borges de Carvalho Nogueira, Eduardo (História da Historiografia: International Journal of Theory and History of Historiography, 2025)
This article aims to present both an unconventional object of analysis (renegades) and an unusual historical-philosophical approach in studies concerning phenomena located in the State of India. A powerful portion of the Portuguese Empire, this region hosted the only inquisitorial court established overseas by the Portuguese Crown, which, through its investigative procedures generating valuable documentation, made it possible to access the life experiences of six men identified as apostates and renegades. Thus, drawing on concepts from Agamben’s philosophy (the sacred and the profane) and Foucault (transgression) to understand the phenomenon of renegation among subjects of the Catholic Crown in India between the 16th and 17th centuries, this work seeks to propose a historiographical perspective that goes beyond merely recounting past experiences, instead delving into them in greater depth.